PUBLIC POLICY IMPLEMENTATION IN THE LOCAL SOCIO-CULTURAL CONTEXT AS A TRANSITION FROM REGULATION TO REALITY - Syarif, Kurnia Ali; Manda, Darman; Darmayanti, Dyan Paramitha (Jurnal Aktor, 2025)
This research aims to examine the influence of the local socio-cultural context on the implementation of public policies in Indonesia and the obstacles that occur in the transition of policies from central regulations to reality on the ground. Based on a literature review approach, this research analyzes public policies such as the Village Fund and smart city development that face major challenges when they do not consider local cultural values. The findings show that policies that are not adapted to local culture, such as gotong royong in villages or the kinship system in Madura, often encounter obstacles in implementation. In addition, the transition of policies from central regulations to reality in the regions is also often constrained by the mismatch between central policies and the socio-cultural conditions that exist in the field. This research emphasizes the importance of public policy adaptation to local culture to ensure the success of the policy implementation.